Conversion of hydroperoxides to carbonyls in field and laboratory instrumentation: Observational bias in diagnosing pristine versus anthropogenically controlled atmospheric chemistry. Issue 23 (8th December 2014) - Rivera‐Rios, J. C.; Nguyen, T. B.; Crounse, J. D.; Jud, W.; St. Clair, J. M.; Mikoviny, T.; Gilman, J. B.; Lerner, B. M.; Kaiser, J. B.; de Gouw, J.; Wisthaler, A.; Hansel, A.; et al.
Abstract: Atmospheric volatile organic compound (VOC) oxidation mechanisms under pristine (rural/remote) and urban (anthropogenically‐influenced) conditions follow distinct pathways due to large differences in nitrogen oxide (NOx ) concentrations. These two pathways lead to products that have different chemical and physical properties and reactivity. Under pristine conditions, isoprene hydroxy hydroperoxides (ISOPOOHs) are the dominant first‐generation isoprene oxidation products. Utilizing authentic ISOPOOH standards, we demonstrate that two of the most commonly used methods of measuring VOC oxidation products (i.e., gas chromatography and proton transfer reaction mass spectrometry) observe these hydroperoxides as their equivalent high‐NO isoprene oxidation products – methyl vinyl ketone (MVK) and methacrolein (MACR). This interference has led to an observational bias affecting our understanding of global atmospheric processes. Considering these artifacts will help close the gap on discrepancies regarding the identity and fate of reactive organic carbon, revise our understanding of surface‐atmosphere exchange of reactive carbon and SOA formation, and improve our understanding of atmospheric oxidative capacity. Key Points: Hydroperoxides are being observed as their carbonyl analogues in GC and PTR‐MS Interference results in observational bias towards urban conditions The implications of this interference are discussed